High resolution respirometry in diagnostic of mitochondrial disorders caused by mitochondrial complex I deficiency - Krylova, T D; Tsygankova, P G; Itkis, Yu S; Sheremet, N L; Nevinitsyna, T A; Mikhaylova, S V; Zakharova, E Yu (Biomeditsinskaia khimiia, 2017)
Complex I (CI) deficiency is one of the most common defects in the OXPHOS system; it represents more than 30% cases of mitochondrial diseases. The group is characterized by clinical and genetic heterogeneity and comprise several nosological forms. The most prevalent phenotypes for CI are LHON and Leigh syndrome. In this study we have analyzed skin fibroblasts from 11 patients with mutations in mtDNA, which cause LHON or Leigh-like phenotypes: m.11778 G>A (n=3), m.3460 A>G (n=2), m.3635 G>A (n=1), m.3308 T>G (n=2), m.3472 T>C (n=1) and 2 patients with earlier unknown substitutions m.3945 C>A and m.14441T>C. High-resolution respirometry (HRR) on the Oxygraph-2k instrument ("Oroboros corp.", Austria) was performed for complex analysis of the mitochondrial respiratory function in intact and permeabilized fibroblasts of patients and healthy controls. Flux control rations in intact cells R/E, (R-L)/E (p<0.05) were raised compared to the control. Rates of R, E, L normalized on the CS were statistically varied between patients and controls. In permeabilized fibroblasts we observed differences in CII/E, Rot/E, R/CII, CI/CII (p<0.05) between groups. These data highlight the dysfunction of the OXPHOS system and particularly CI. Increased citrate synthase level and decreased CI/CII ratio indicate compensatory metabolic response to respiratory chain dysfunction. Our results show applicability of HRR in revealing the biochemical abnormalities of complex I in fibroblasts of patients with LHON and Leigh-like syndrome. We also suggest HRR to be a useful method for inspection of other mutations causing complex I deficiency.